Features of distribution of receptors to the wheat germ agglutinin (WGA) in the intercellular matrix of the menisci of rat knee joint after intrafetal injection of antigens - Abrosimov, Yu. Yu.; Абросімов, Юрій Юрійович (publishing center of the ESCBM, The Czech Republic, 2018)
The results of previous researches at the Department of Human Anatomy of Zaporizhzhia State Medical University have shown that for the modeling of the syndrome of undifferentiated connective tissue dysplasia in rats it is possible to use the intrauterine antigenic effect that leads to changes in the rates of morphogenesis of fetal organs and tissues [3]. Lectins are informative molecular probes that can detect glycoconjugates in cells and tissues. Lectins and their receptors provide intercellular, cell-matrix interactions, participate in the regulation of proliferation, differentiation and apoptosis of cells [1, 2]. Aim of the work was to establish the features of distribution of receptors to the wheat germ agglutinin (WGA) in the intercellular matrix of the menisci of rat knee joint after intrafetal injection of antigens.
Keywords: lectins; germ agglutinin receptors; dysplasia